2023
DOI: 10.1039/d2ce01202b
|View full text |Cite
|
Sign up to set email alerts
|

Graphite/diamond transformation mechanism under the action of an iron-based catalyst

Abstract: Although it has been near 70 years since iron-based catalyst was used to synthesize diamond from graphite at high pressure and high temperature (HPHT), the graphite to diamond transformation mechanism...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…To obtain a temperature gradient, the sample is slightly off center as shown in Figure a because there is a temperature decrease from the cell center to the two ends of the cylindrical sample chamber with a temperature difference of 70 °C. The thus-determined high- P – T formation diagrams are plotted in Figure c–f, showing a similar valley shape of formation regions for different nitrides, distinct from previous reports with a narrow valley shape that might be tentatively depicted based on limited experiment data …”
Section: Resultssupporting
confidence: 41%
See 3 more Smart Citations
“…To obtain a temperature gradient, the sample is slightly off center as shown in Figure a because there is a temperature decrease from the cell center to the two ends of the cylindrical sample chamber with a temperature difference of 70 °C. The thus-determined high- P – T formation diagrams are plotted in Figure c–f, showing a similar valley shape of formation regions for different nitrides, distinct from previous reports with a narrow valley shape that might be tentatively depicted based on limited experiment data …”
Section: Resultssupporting
confidence: 41%
“…The thus-determined high-P− T formation diagrams are plotted in Figure 1c−f, showing a similar valley shape of formation regions for different nitrides, distinct from previous reports with a narrow valley shape that might be tentatively depicted based on limited experiment data. 35 Using Ca 3 N 2 as a catalyst, the required minimum pressure for the formation of cBN is as high as 4.8 GPa, which is by contrast to that of Mg 3 N 2 and Sr 3 N 2 with a nearly same minimum pressure of ∼3.8 GPa. An intermediate pressure value of ∼4.5 GPa is observed for Li 3 N. According to these P− T diagrams, the lower limit of formation temperature for Li 3 N, Mg 3 N 2 , and Ca 3 N 2 is in the 1300−1350 °C range, slightly higher than that of Sr 3 N 2 (i.e., 1200 °C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 7 ] It is found that the catalytic effect of iron oxide is very impressive in the middle‐ and high‐temperature ranges. [ 11 ] It is found that loading Mn‐, Ce‐, and Fe‐based oxides on the catalyst can improve the de‐NO x effect of SCR. [ 9,12,13 ] Liang and Gui [ 14 ] verified the de‐NO x activity of the γ‐Fe 2 O 3 catalyst.…”
Section: Introductionmentioning
confidence: 99%